How to build a theory in cognitive science - Hardcastle, Valerie Gray (SUNY series in philosophy and biology., 1996)
How to Build a Theory in Cognitive Science specifies the characteristics of fruitful interdisciplinary theories in cognitive science and shows how they differ from the successful theories in the individual disciplines composing the cognitive sciences. It articulates a method for integrating the various disciplines successfully so that unified, truly interdisciplinary theories are possible. This book makes three contributions of utmost importance. First, it provides a long-overdue, systematic examination of the field of cognitive science itself. Second, it provides a template for linking domains without loss of autonomy. This philosophical treatment of integration serves as a blueprint for future endeavors. Third, the book provides a solid theoretical foundation that will prevent future missteps and enhance collaboration.